A positive electrode material, a preparation method thereof, a pole piece and a battery

CN122977338APending Publication Date: 2026-10-27SHANGHAI SUNRISE POLYMER MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610786448.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-02
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0004]本发明要解决的技术问题是为了克服现有技术中的聚氨酯作为制备正极材料的碳源存在一些不足导致所得正极材料制得的电池电化学性能较差的缺陷,提供一种正极材料及其制备方法、极片和电池

Benefits of technology

采用本申请的正极材料制得的正极材料具有较低的粉末电阻率、较高的粉末电导率和较佳的压实密度;由该正极材料制得的电池具有优异的电化学性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122977338A_ABST
    Figure CN122977338A_ABST
Patent Text Reader

Abstract

The application discloses a positive electrode material and a preparation method thereof, a pole piece and a battery. The preparation method of the positive electrode material comprises the following steps: sintering a precursor slurry to obtain the positive electrode material; the precursor slurry comprises a carbon source; the carbon source comprises polyether modified polyurethane; and the polyether modified polyurethane is prepared by using polyether polyol and isocyanate as raw materials. The positive electrode material prepared by using the preparation method of the positive electrode material has low powder resistivity, high powder conductivity and good compactness; and the battery prepared from the positive electrode material has excellent electrochemical performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a positive electrode material, its preparation method, an electrode sheet, and a battery. Background Technology

[0002] Currently, lithium-ion battery cathode materials generally employ organic polymer pyrolytic carbon coating to improve electronic conductivity and suppress interfacial side reactions and lattice collapse. Among them, polyurethane (PU) is widely used as a carbon coating precursor due to its advantages such as nitrogen self-doping, excellent film-forming properties, high pyrolytic carbon yield, and good interfacial wettability with cathode particles.

[0003] However, existing technologies using conventional polyurethane as a carbon source still suffer from the following core drawbacks, severely limiting the electrochemical performance of cathode materials: Firstly, conventional polyurethane has poor water solubility. When directly added to the cathode material precursor slurry, the polyurethane cannot dissolve and exists only as solid particles. During subsequent sintering, the residual carbon produced by the solid polyurethane cannot form a uniform coating on the surface of the cathode material particles, significantly increasing the powder resistivity and reducing conductivity, thus affecting the performance of lithium-ion batteries. Secondly, existing technologies involve separately adding the raw materials for polyurethane preparation to the precursor, allowing the polyurethane reaction to occur within the cathode material precursor system. However, this method cannot control the reaction rate and extent of the polyurethane reaction, resulting in poor reproducibility and failing to ensure uniform distribution of polyurethane in the precursor, further impacting the performance of the cathode material. Summary of the Invention

[0004] The technical problem this invention aims to solve is to overcome the shortcomings of existing technologies that use polyurethane as a carbon source for preparing cathode materials, resulting in poor electrochemical performance of batteries made from the obtained cathode materials. This invention provides a cathode material, its preparation method, an electrode sheet, and a battery. The cathode material prepared using the method of this application has low powder resistivity, high powder conductivity, and good compaction density; the battery made from this cathode material exhibits excellent electrochemical performance.

[0005] The present invention solves the above-mentioned technical problems through the following technical solution: This invention provides a method for preparing a cathode material, comprising the following steps: The precursor slurry is sintered to obtain the cathode material; the precursor slurry includes a carbon source; the carbon source includes polyether-modified polyurethane. The polyether-modified polyurethane is prepared using polyether polyol and isocyanate as raw materials.

[0006] In this invention, the weight-average molecular weight of the polyether-modified polyurethane can be 2000-5000, preferably 2010-4000, such as 2015, 3597, 2833, 2367 or 2519.

[0007] In this invention, the PDI of the polyether-modified polyurethane can be 1.00-2.00, preferably 1.03-1.20, such as 1.038560, 1.102502, 1.102931, 1.046140 or 1.031904.

[0008] In this invention, the polyether polyol is preferably polyether diol and / or polyether triol.

[0009] The polyether diol preferably has the structure described in Formula I: Formula I; In Formula I, the values ​​of a, b, and c are each independently between 0 and 500, and a, b, and c cannot be 0 simultaneously; preferably, a = c; the value of a is preferably between 10 and 50, for example, 13. The value of b is preferably between 10 and 50, for example, 30. The value of c is preferably between 10 and 50, for example, 13.

[0010] The polyether diol preferably has the structure described in Formula II: Formula II; In Formula II, the values ​​of d, e, and f are each independently between 0 and 500, and a, b, and c cannot be 0 simultaneously; preferably, d = f. The value of d is preferably between 10 and 50, for example, 14. The value of e is preferably between 10 and 50, for example, 24. The value of f is preferably between 10 and 50, for example, 14.

[0011] The polyether triol preferably has the structure described in Formula III: Formula III; In Formula III, R1, R2, and R3 are each independently selected from -H, -CH3, or -CH2CH3, and the values ​​of g, h, and i are each independently between 0 and 500, and g, h, and i cannot be 0 simultaneously. g is preferably 1-20, for example, 6. h is preferably 1-20, for example, 6. i is preferably 1-20, for example, 6.

[0012] In this invention, the hydroxyl value of the polyether polyol can be 20-500 mgKOH / g, preferably 30-300 mgKOH / g, for example 280.5, 38.9, 42.3 or 190.4 mgKOH / g.

[0013] In a preferred embodiment, the polyether glycol is polyethylene glycol 400 with a hydroxyl value of 280.5 mg KOH / g.

[0014] In a preferred embodiment, the polyether diol is propylene glycol block polyether Pluronic L64 with a hydroxyl value of 38.9 mg KOH / g.

[0015] In a preferred embodiment, the polyether diol is trans polyether Pluronic 17R4 with a hydroxyl value of 42.3 mg KOH / g.

[0016] In a preferred embodiment, the polyether triol is glycerol polyoxyethylene ether G18 with a hydroxyl value of 190.4 mg KOH / g.

[0017] In this invention, the isocyanate can be of conventional types in the art, preferably toluene isocyanate and / or toluene diisocyanate. The toluene isocyanate is preferably one or more of o-toluene isocyanate, m-toluene isocyanate, and p-toluene isocyanate, for example, m-toluene isocyanate. The toluene diisocyanate is a mixture of toluene-2,4-diisocyanate and toluene-2,6-diisocyanate. The mass ratio of toluene-2,4-diisocyanate to toluene-2,6-diisocyanate is (1-6):1, for example, 1:1.

[0018] In this invention, the molar ratio of the polyether polyol to the isocyanate can be (1-15):1, preferably (1-10):1, for example 1:1, 2:1, 3:1 or 4:1.

[0019] In this invention, the raw materials for the polyether-modified polyurethane preferably also include a catalyst.

[0020] The catalyst can be of conventional types in the art, preferably a tin-based catalyst and / or an amine catalyst. The tin-based catalyst is preferably dibutyltin dilaurate and / or stannous octoate. The amine catalyst is preferably triethylenediamine.

[0021] The catalyst is preferably used in an amount of 0.01-5.0 php, more preferably in an amount of 0.03-0.3 php, such as 0.05, 0.07, 0.13, 0.25 or 0.19 php. The php refers to the mass percentage of the catalyst relative to the polyether polyol and isocyanate.

[0022] In a preferred embodiment 1, the polyether-modified polyurethane is prepared using polyethylene glycol 400, toluene diisocyanate, and dibutyltin dilaurate as raw materials.

[0023] In a preferred embodiment 2, the polyether-modified polyurethane is prepared using propylene glycol block polyether Pluronic L64, toluene diisocyanate, and stannous octoate as raw materials.

[0024] In a preferred embodiment 3, the polyether-modified polyurethane is prepared using trans-polyether Pluronic 17R4, toluene diisocyanate, and stannous octoate as raw materials.

[0025] In a preferred embodiment 4, the polyether-modified polyurethane is prepared using glycerol polyoxyethylene ether G18, toluene diisocyanate and triethylenediamine as raw materials.

[0026] In a preferred embodiment 5, the polyether-modified polyurethane is prepared using glycerol polyoxyethylene ether G18, m-toluene isocyanate and dibutyltin dilaurate as raw materials.

[0027] In this invention, the preparation method of the polyether-modified polyurethane preferably includes the following steps: adding the isocyanate dropwise to the mixture of the polyether polyol and the catalyst, and reacting.

[0028] The mixture of polyether polyol and catalyst is obtained by mixing and stirring the polyether polyol and catalyst. The stirring time is preferably 30-120 min, for example, 30, 40 or 50 min.

[0029] The preferred dripping time for the isocyanate is 30-100 min, for example, 40, 50, 60, 70 or 90 min.

[0030] The preferred temperature of the system during the addition of the isocyanate is 25-75°C.

[0031] The reaction temperature is preferably 25-75℃, for example 50, 55, 65, 70 or 75℃.

[0032] The reaction time is preferably 60-120 min, for example 60, 80, 90, 100 or 120 min.

[0033] In this invention, the mass percentage of the carbon source can be 3-15%, preferably 5-12%, for example 9.5%, 8.9%, 8.2%, 6.1%, 5.5%, 5.3% or 12%; the mass percentage represents the mass percentage of the carbon source in the precursor slurry excluding the solvent.

[0034] In this invention, the polyether-modified polyurethane accounts for 30-70% of the mass percentage of the carbon source, preferably 45-60%, for example 53.8%, 50%, 45.5%, 57.1% or 52.6%.

[0035] In this invention, the carbon source preferably also includes other carbon sources, more preferably one or more selected from sucrose, glucose, polyethylene glycol, starch, citric acid, and asphalt, such as polyethylene glycol and / or glucose. The polyethylene glycol is preferably PEG1500, PEG6000, or PEG-200.

[0036] In a preferred embodiment, the carbon source comprises glucose and the polyether-modified polyurethane. The mass ratio of glucose to the polyether-modified polyurethane may be (0.3-2):1, preferably (0.5-1.5):1, for example 6:7, 0.75:1, 0.9:1, 1:1 or 1.2:1.

[0037] In this invention, the precursor slurry preferably also includes raw materials conventional in the art.

[0038] In this invention, the type of positive electrode material can be conventional in the art, such as lithium iron phosphate, lithium manganese iron phosphate, or sodium iron manganese phosphate.

[0039] In this invention, the sintering temperature can be 300-850℃, preferably 400-750℃, for example 480, 550, 700 or 720℃. The sintering time can be 1-20h, preferably 2-13h, for example 2, 7, 8 or 12h.

[0040] In this invention, the sintering is preferably carried out under an inert atmosphere, such as a nitrogen atmosphere.

[0041] In this invention, the heating rate from room temperature to the sintering temperature is preferably 1-10°C / min, more preferably 2-6°C / min, for example 3 or 5°C / min.

[0042] In this invention, the sintering is preferably divided into a single-stage sintering and a two-stage sintering, wherein the temperature of the two-stage sintering is higher than that of the single-stage sintering.

[0043] The sintering temperature of the first stage is preferably 300-600℃, more preferably 400-500℃, for example 480℃. The sintering time of the first stage is preferably 1-4h, more preferably 2-3h, for example 2h. The heating rate from room temperature to the sintering temperature of the first stage is preferably 3-8℃ / min, more preferably 4-6℃ / min, for example 5℃ / min.

[0044] The preferred temperature for the second-stage sintering is 500-850℃, more preferably 650-750℃, for example 700℃. The preferred sintering time for the second stage is 5-10 hours, more preferably 7-9 hours, for example 8 hours. The heating rate from the temperature of the first-stage sintering to the temperature of the second-stage sintering is preferably 1-5℃ / min, more preferably 2-4℃ / min, for example 3℃ / min.

[0045] In a preferred embodiment, the cathode material is lithium iron phosphate, and the preparation method of the cathode material includes the following steps: spray granulation and sintering of the precursor slurry; the precursor slurry includes an iron source, a lithium source, a phosphorus source, a carbon source and a solvent; the carbon source includes polyether-modified polyurethane and glucose.

[0046] The iron source can be of a type conventional in the art, such as iron phosphate. The lithium source can be of a type conventional in the art, such as lithium carbonate. The phosphorus source can be of a type conventional in the art, such as phosphoric acid. The phosphorus source is generally added in the form of an aqueous phosphoric acid solution. The mass concentration of phosphoric acid in the aqueous phosphoric acid solution is preferably 75-90 wt%, for example, 85 wt%. The mass ratio of glucose to the polyether-modified polyurethane can be (0.3-2):1, preferably (0.5-1.5):1, for example, 6:7, 1:1 or 1.2:1. The solvent can be of a type conventional in the art, such as water. The preferred mass ratio of the iron source, lithium source, phosphorus source and carbon source is (800-1200):(200-300):(3-9):(80-160), more preferably (900-1100):(210-240):(5-8):(100-140), for example 995:226:6.73:120, 995:226:6.73:130 or 995:226:6.73:110.

[0047] The solid content of the precursor slurry is preferably 30-60%, more preferably 35-50%, for example 40%. The D50 of the precursor slurry is preferably 250-500nm, more preferably 350-400nm, for example 370-380nm.

[0048] The precursor slurry is preferably obtained by mixing an iron source, a lithium source, a phosphorus source, a carbon source, and a solvent, followed by sand milling. The sand milling time is preferably 60-180 min, more preferably 90-150 min, for example 120 min.

[0049] The precursor slurry preferably also includes a metal dopant. The metal dopant is preferably one or more of a Ti compound, a V compound, and a Nb compound, more preferably a Ti compound, such as titanium dioxide. The mass ratio of the metal dopant to the iron source is preferably (800-1200):(3-9), more preferably (900-1100):(5-7), for example 995:5.97.

[0050] The spray granulation temperature is preferably 180-300℃, more preferably 200-240℃, for example 220℃. During spray granulation, the flow rate of the precursor slurry is preferably 600-1000 ml / h, more preferably 700-900 ml / h, for example 800 ml / h.

[0051] In a preferred embodiment, the cathode material is lithium manganese iron phosphate, and the preparation method of the cathode material includes the following steps: sintering a precursor slurry; the precursor slurry includes a lithium source, a manganese source, an iron source, a phosphorus source, a carbon source, and a solvent; the carbon source includes polyether-modified polyurethane and glucose.

[0052] The lithium source can be of a type conventional in the art, such as lithium carbonate. The manganese source can be of a type conventional in the art, such as manganese acetate. The iron source can be of a type conventional in the art, such as ferrous oxalate. The phosphorus source can be of a type conventional in the art, such as phosphoric acid. The mass ratio of glucose to the polyether-modified polyurethane can be (0.3-2):1, preferably (0.5-1.5):1, for example 0.75:1, 1:1 or 0.9:1. The solvent can be of a type conventional in the art, such as anhydrous ethanol. The preferred mass ratio of the lithium source, manganese source, iron source, phosphorus source, carbon source and solvent is (200-500):(1000-1500):(5-15):(8-20):(50-150):(500-1500), more preferably (300-400):(150-300):(7-11):(10-15):(70-110):(800-1200), for example 350:1250:9:12:90:1000, 350:1250:9:12:95:1000 or 350:1250:9:12:105:1000.

[0053] The precursor slurry is preferably obtained by ball milling a lithium source, a manganese source, an iron source, a phosphorus source, a carbon source, and a solvent. The ball milling speed is preferably 200-400 r / min, more preferably 250-300 r / min, for example, 280 r / min. The ball milling time is preferably 1-7 h, more preferably 3-5 h, for example, 4 h. The ball-to-material ratio during ball milling is preferably (4-12):1, more preferably (6-10):1, for example, 8:1.

[0054] Prior to sintering, the precursor slurry preferably undergoes a process of solvent removal and particle size control. The solvent removal method can be conventional in the art, such as vacuum drying. The vacuum drying temperature is preferably 40-70°C, more preferably 50-60°C, for example 55°C. The vacuum drying time is preferably 5-12 hours, more preferably 6-10 hours, for example 8 hours. The particle size control method can be conventional in the art, such as grinding. The endpoint of particle size control is preferably that the material can pass through a 100-mesh sieve.

[0055] The sintering is preferably divided into a single-stage sintering and a two-stage sintering, wherein the temperature of the two-stage sintering is higher than that of the single-stage sintering.

[0056] The sintering temperature of the first stage is preferably 300-600℃, more preferably 400-500℃, for example 480℃. The sintering time of the first stage is preferably 1-4h, more preferably 2-3h, for example 2h. The heating rate from room temperature to the sintering temperature of the first stage is preferably 3-8℃ / min, more preferably 4-6℃ / min, for example 5℃ / min.

[0057] The preferred temperature for the second-stage sintering is 500-850℃, more preferably 650-750℃, for example 700℃. The preferred sintering time for the second stage is 5-10 hours, more preferably 7-9 hours, for example 8 hours. The heating rate from the temperature of the first-stage sintering to the temperature of the second-stage sintering is preferably 1-5℃ / min, more preferably 2-4℃ / min, for example 3℃ / min.

[0058] In a preferred embodiment, the cathode material is sodium iron manganese phosphate, and the preparation method of the cathode material includes the following steps: calcining a precursor slurry; the precursor slurry includes a sodium source, a phosphorus source, an iron source, a manganese source, a carbon source, and a solvent; the carbon source includes polyether-modified polyurethane and glucose.

[0059] The sodium source can be of a conventional type in the art, such as sodium carbonate. The phosphorus source can be of a conventional type in the art, such as ammonium dihydrogen phosphate. The iron source can be of a conventional type in the art, such as ferric oxide. The manganese source can be of a conventional type in the art, such as manganese dioxide. The mass ratio of glucose to polyether-modified polyurethane can be (0.3-2):1, preferably (0.5-1.5):1, for example 0.75:1, 1:1 or 0.9:1. The solvent can be of a conventional type in the art, such as water. Based on sodium, iron, manganese and phosphorus elements, the molar ratio of sodium source, phosphorus source, iron source and manganese source is preferably (1-9):(1-5):(0.01-0.1):(1-9), more preferably (3-5):(2-4):(0.01-0.03):(3-5), for example 4:2.98:0.01:4. The molar ratio of the carbon source to the iron and manganese sources, calculated by carbon, iron and manganese elements, is preferably (0.2-1):(0.5-3), more preferably (0.3-1):(0.8-1.5), for example 0.5:1.

[0060] The solid content of the precursor slurry is preferably 30-60 wt%, more preferably 45-55 wt%, for example 50 wt%.

[0061] The precursor slurry is preferably obtained by mixing a sodium source, a phosphorus source, an iron source, a manganese source, a carbon source, and a solvent, followed by sand milling. The sand milling speed is preferably 1400-2600 r / min, more preferably 1800-2200 r / min, for example, 2000 r / min. The sand milling time is preferably 3-10 h, more preferably 5-7 h, for example, 6 h.

[0062] The sintering temperature can be 300-850℃, preferably 400-750℃, for example 480, 550, 700 or 720℃. The sintering time can be 1-20h, preferably 2-13h, for example 2, 7, 8, 10 or 12h. The heating rate from room temperature to the sintering temperature is preferably 1-10℃ / min, more preferably 2-6℃ / min, for example 3 or 5℃ / min.

[0063] In this invention, the water solubility of the polyether-modified polyurethane is improved by introducing polyether chains into the polyurethane structure. The water-soluble polyether-modified polyurethane is used as a carbon source and added to the precursor slurry, where it can be completely dissolved. During subsequent sintering, this improves the uniformity of carbon source coating, thereby enhancing the electrochemical performance of the battery made from the resulting cathode material. Preferably, the polyether-modified polyurethane of this invention contains benzene rings with a rigid structure, which not only increases the carbon content of the cathode material and reduces the amount of carbon source added and the raw material cost of the cathode material, but more importantly, using the benzene-ring-containing polyether-modified polyurethane as a carbon source after sintering can generate ordered graphitized coated carbon, thereby improving the electrochemical performance of the battery made from the resulting cathode material.

[0064] This invention provides a cathode material, which is prepared using the cathode material preparation method described above.

[0065] The present invention provides an electrode sheet comprising the positive electrode material as described above.

[0066] The present invention provides a battery comprising the electrodes as described above.

[0067] In this invention, the battery may be a lithium-ion battery or a sodium-ion battery.

[0068] The positive and progressive effects of this invention are as follows: The cathode material prepared using the cathode material of this application has low powder resistivity, high powder conductivity and good compaction density; the battery prepared using the cathode material has excellent electrochemical performance. Attached Figure Description

[0069] Figure 1 The image shows the infrared spectrum of the polyether-modified polyurethane prepared in Example 1.

[0070] Figure 2 The image shows the infrared spectrum of the polyether-modified polyurethane prepared in Example 2.

[0071] Figure 3 The image shows the infrared spectrum of the polyether-modified polyurethane prepared in Example 3.

[0072] Figure 4 The infrared spectrum of the polyether-modified polyurethane prepared in Example 4 is shown.

[0073] Figure 5 The image shows the infrared spectrum of the polyether-modified polyurethane prepared in Example 5.

[0074] Figure 6 The graph shows the molecular weight and PDI test results of the polyether-modified polyurethane prepared in Example 1.

[0075] Figure 7The graph shows the molecular weight and PDI test results of the polyether-modified polyurethane prepared in Example 2.

[0076] Figure 8 The graph shows the molecular weight and PDI test results of the polyether-modified polyurethane prepared in Example 3.

[0077] Figure 9 The graph shows the molecular weight and PDI test results of the polyether-modified polyurethane prepared in Example 4.

[0078] Figure 10 The graph shows the molecular weight and PDI test results of the polyether-modified polyurethane prepared in Example 5.

[0079] Figure 11 This is a SEM image of the lithium iron phosphate cathode material prepared in Example 1.

[0080] Figure 12 The image shows the SEM image of the lithium iron phosphate cathode material prepared in Comparative Example 1. Detailed Implementation

[0081] The present invention will be further illustrated by way of embodiments below, but the present invention is not limited to the scope of the embodiments described herein.

[0082] I. Preparation of Lithium Iron Phosphate Cathode Material

[0083] Example 1

[0084] 1. Preparation of polyether-modified polyurethane: Polyether polyol (PEG400) was added to a reactor equipped with a stirrer and a heater. A catalyst (dibutyltin dilaurate) was added to the reactor at a rate of 0.05 php. The mixture was stirred for 30 min, and then isocyanate (toluene diisocyanate, toluene-2,4-diisocyanate, and toluene-2,6-diisocyanate in a mass ratio of 4:1) was added dropwise. The molar ratio of PEG400 to toluene diisocyanate was 3:1. The dropwise addition of toluene diisocyanate took 60 min, and the temperature was controlled between 25-75℃ throughout the dropwise addition process. After the dropwise addition was completed, the reaction was allowed to proceed for 60 min at a temperature of 65℃. After the reaction was completed, the product was discharged to obtain polyether-modified polyurethane PU-1.

[0085] 2. Preparation of lithium iron phosphate cathode material: 995 parts of ferric phosphate, 226 parts of lithium carbonate, 6.73 parts of 85wt% phosphoric acid aqueous solution, 5.97 parts of titanium dioxide, 60 parts of glucose, and 70 parts of polyether-modified polyurethane PU-1 were added to a sand mill (WSP-0.5 from Changzhou Longxin Intelligent Equipment Co., Ltd.) along with the corresponding amount of water. The mixture was sand-milled for 120 minutes to obtain a precursor slurry with a solid content of 40% and a particle size D50 of 370-380 nm. The carbon source accounted for 9.5% of the total carbon source mass, representing the percentage of carbon source in the precursor slurry excluding the solvent. The polyether-modified polyurethane accounted for 53.8% of the carbon source mass. The precursor slurry was spray-granulated in a spray granulation equipment (SP1500 from Shanghai Shunyi Experimental Equipment Co., Ltd.), with an inlet temperature of 220℃ and a material flow rate of 800ml / h. The spray-granulated powder was sintered (using a QLYF-4-1200 sintering equipment from Shanghai Jingzhao Machinery Equipment Co., Ltd.), with a heating rate of 3℃ / min to 720℃ and a holding time of 7h to obtain lithium iron phosphate material.

[0086] The obtained lithium iron phosphate material was crushed to powder with a particle size D50 of 1.2-1.3 μm using a traditional Chinese medicine crusher. The traditional Chinese medicine crusher was a Teruis traditional Chinese medicine pulverizer, and the particle size was tested using a Malvern Panaco Mastersizer-3000 laser particle size analyzer.

[0087] Example 2

[0088] 1. Preparation of polyether-modified polyurethane: Polyether polyol (propylene glycol block polyether Pluronic L64) was added to a reactor equipped with a stirrer and a heater. Catalyst (stannous octoate) was added to the reactor at a rate of 0.07 php. The mixture was stirred for 40 min, and then isocyanate (toluene diisocyanate) was added dropwise. The molar ratio of Pluronic L64 to toluene diisocyanate was 2:1. The dropwise addition of toluene diisocyanate took 50 min. The temperature was controlled between 25-75℃ throughout the dropwise addition process. After the dropwise addition was completed, the reaction was allowed to proceed for 80 min at a reaction temperature of 70℃. After the reaction was completed, the product was discharged to obtain polyether-modified polyurethane PU-2.

[0089] 2. Preparation of lithium iron phosphate cathode material: 995 parts of ferric phosphate, 226 parts of lithium carbonate, 6.73 parts of 85wt% phosphoric acid aqueous solution, 5.97 parts of titanium dioxide, 60 parts of glucose, and 60 parts of polyether-modified polyurethane PU-2 were added to a sand mill (WSP-0.5 from Changzhou Longxin Intelligent Equipment Co., Ltd.) along with the corresponding amount of water. The milling process lasted 120 minutes to obtain a precursor slurry with a solid content of 40% and a particle size D50 of 370-380 nm. The carbon source accounted for 8.9% of the total carbon source mass, representing the percentage of carbon source in the precursor slurry excluding the solvent. The polyether-modified polyurethane accounted for 50% of the carbon source mass. The precursor slurry was spray-granulated in a spray granulation equipment (SP1500 from Shanghai Shunyi Experimental Equipment Co., Ltd.), with an inlet temperature of 220℃ and a material flow rate of 800ml / h. The spray-granulated powder was sintered (using a QLYF-4-1200 sintering equipment from Shanghai Jingzhao Machinery Equipment Co., Ltd.), with a heating rate of 3℃ / min to 720℃ and a holding time of 7h to obtain lithium iron phosphate material.

[0090] Example 3

[0091] 1. Preparation of polyether-modified polyurethane: Polyether polyol (trans-polyether Pluronic 17R4) was added to a reactor equipped with a stirrer and a heater. Catalyst (stannous octoate) was added to the reactor at a rate of 0.13 php. The mixture was stirred for 50 min, and then isocyanate (toluene diisocyanate) was added dropwise. The molar ratio of Pluronic 17R4 to toluene diisocyanate was 4:1. The dropwise addition of toluene diisocyanate took 70 min, and the temperature was controlled between 25-75℃ throughout the dropwise addition process. After the dropwise addition was completed, the reaction was allowed to proceed for 90 min at a reaction temperature of 75℃. After the reaction was completed, the product was discharged to obtain polyether-modified polyurethane PU-3.

[0092] 2. Preparation of lithium iron phosphate cathode material: 995 parts of ferric phosphate, 226 parts of lithium carbonate, 6.73 parts of 85wt% phosphoric acid aqueous solution, 5.97 parts of titanium dioxide, 60 parts of glucose, and 60 parts of polyether-modified polyurethane PU-3 were added to a sand mill (WSP-0.5 from Changzhou Longxin Intelligent Equipment Co., Ltd.) along with the corresponding amount of water. The mixture was sand-milled for 120 minutes to obtain a precursor slurry with a solid content of 40% and a particle size D50 of 370-380 nm. The carbon source accounted for 8.9% of the total carbon source mass, representing the percentage of carbon source in the precursor slurry excluding the solvent. The polyether-modified polyurethane accounted for 50% of the carbon source mass. The precursor slurry was spray-granulated in a spray granulation equipment (SP1500 from Shanghai Shunyi Experimental Equipment Co., Ltd.), with an inlet temperature of 220℃ and a material flow rate of 800ml / h. The spray-granulated powder was sintered (using a QLYF-4-1200 sintering equipment from Shanghai Jingzhao Machinery Equipment Co., Ltd.), with a heating rate of 3℃ / min to 720℃ and a holding time of 7h to obtain lithium iron phosphate material.

[0093] Example 4

[0094] 1. Preparation of polyether-modified polyurethane: Polyether polyol (glycerol polyoxyethylene ether G18) was added to a reactor equipped with a stirrer and a heater. A catalyst (triethylenediamine) was added to the reactor at a rate of 0.25 php. The mixture was stirred for 30 min, and then isocyanate (toluene diisocyanate) was added dropwise. The molar ratio of G18 to toluene diisocyanate was 3:1, and the dropwise addition time was 90 min. The temperature during the entire dropwise addition process was controlled at 25-75℃. After the dropwise addition was completed, the reaction was allowed to proceed for 120 min at a reaction temperature of 50℃. After the reaction was completed, the product was discharged to obtain polyether-modified polyurethane PU-4.

[0095] 2. Preparation of lithium iron phosphate cathode material: 995 parts of ferric phosphate, 226 parts of lithium carbonate, 6.73 parts of 85wt% phosphoric acid aqueous solution, 5.97 parts of titanium dioxide, 60 parts of glucose, and 50 parts of polyether-modified polyurethane PU-4 were added to a sand mill (WSP-0.5 from Changzhou Longxin Intelligent Equipment Co., Ltd.) along with the corresponding amount of water. The milling process lasted 120 minutes to obtain a precursor slurry with a solid content of 40% and a particle size D50 of 370-380 nm. The carbon source accounted for 8.2% of the total carbon source mass, representing the percentage of carbon source in the precursor slurry excluding the solvent. The polyether-modified polyurethane accounted for 45.5% of the carbon source mass. The precursor slurry was spray-granulated in a spray granulation equipment (SP1500 from Shanghai Shunyi Experimental Equipment Co., Ltd.), with an inlet temperature of 220℃ and a material flow rate of 800ml / h. The spray-granulated powder was sintered (using a QLYF-4-1200 sintering equipment from Shanghai Jingzhao Machinery Equipment Co., Ltd.), with a heating rate of 3℃ / min to 720℃ and a holding time of 7h to obtain lithium iron phosphate material.

[0096] Example 5

[0097] 1. Preparation of polyether-modified polyurethane: Polyether polyol (glycerol polyoxyethylene ether G18) was added to a reactor equipped with a stirrer and a heater. Catalyst (dibutyltin dilaurate) was added to the reactor at a rate of 0.19 php. The mixture was stirred for 40 min, and then isocyanate (m-toluene isocyanate) was added dropwise. The molar ratio of G18 to m-toluene isocyanate was 1:1. The dropwise addition of m-toluene isocyanate took 40 min. The temperature during the entire dropwise addition process was controlled between 25-75℃. After the dropwise addition was completed, the reaction was allowed to proceed for 100 min at a reaction temperature of 55℃. After the reaction was completed, the product was discharged to obtain polyether-modified polyurethane PU-5.

[0098] 2. Preparation of lithium iron phosphate cathode material: 995 parts of ferric phosphate, 226 parts of lithium carbonate, 6.73 parts of 85wt% phosphoric acid aqueous solution, 5.97 parts of titanium dioxide, 60 parts of glucose, and 70 parts of polyether-modified polyurethane PU-5 were added to a sand mill (WSP-0.5 from Changzhou Longxin Intelligent Equipment Co., Ltd.) along with the corresponding amount of water. The mixture was sand-milled for 120 minutes to obtain a precursor slurry with a solid content of 40% and a particle size D50 of 370-380 nm. The carbon source accounted for 9.5% of the total carbon source mass, representing the percentage of carbon source in the precursor slurry excluding the solvent. The polyether-modified polyurethane accounted for 53.8% of the carbon source mass. The precursor slurry was spray-granulated in a spray granulation equipment (SP1500 from Shanghai Shunyi Experimental Equipment Co., Ltd.), with an inlet temperature of 220℃ and a material flow rate of 800ml / h. The spray-granulated powder was sintered (using a QLYF-4-1200 sintering equipment from Shanghai Jingzhao Machinery Equipment Co., Ltd.), with a heating rate of 3℃ / min to 720℃ and a holding time of 7h to obtain lithium iron phosphate material.

[0099] Comparative Example 1

[0100] Preparation of lithium iron phosphate cathode material: 995 parts of ferric phosphate, 226 parts of lithium carbonate, 6.73 parts of 85wt% phosphoric acid aqueous solution, 5.97 parts of titanium dioxide, 60 parts of glucose, and 60 parts of Covestro Impranil DLN SD polyurethane dispersion (solid content of 40%) were added to a sand mill (WSP-0.5 of Changzhou Longxin Intelligent Equipment Co., Ltd.) and water was added. The mixture was sand milled for 120 minutes to obtain a precursor slurry with a solid content of 40% and a particle size D50 of 370-380nm. The precursor slurry was spray-granulated in a spray granulation equipment (SP1500 from Shanghai Shunyi Experimental Equipment Co., Ltd.), with an inlet temperature of 220℃ and a material flow rate of 800ml / h. The spray-granulated powder was sintered (using a QLYF-4-1200 sintering equipment from Shanghai Jingzhao Machinery Equipment Co., Ltd.), with a heating rate of 3℃ / min to 720℃ and a holding time of 7h to obtain lithium iron phosphate material.

[0101] Comparative Example 2

[0102] Preparation of lithium iron phosphate cathode material: 995 parts of ferric phosphate, 226 parts of lithium carbonate, 6.73 parts of 85wt% phosphoric acid aqueous solution, 5.97 parts of titanium dioxide, 60 parts of glucose and 70 parts of Lubrizol Sancure 777 waterborne polyurethane (solid content of 35%) were added to a sand mill (WSP-0.5 of Changzhou Longxin Intelligent Equipment Co., Ltd.) and water was added. The mixture was sand milled for 120 minutes to obtain a precursor slurry with a solid content of 40% and a particle size D50 of 370-380nm. The precursor slurry was spray-granulated in a spray granulation equipment (SP1500 from Shanghai Shunyi Experimental Equipment Co., Ltd.), with an inlet temperature of 220℃ and a material flow rate of 800ml / h. The spray-granulated powder was sintered (using a QLYF-4-1200 sintering equipment from Shanghai Jingzhao Machinery Equipment Co., Ltd.), with a heating rate of 3℃ / min to 720℃ and a holding time of 7h to obtain lithium iron phosphate material.

[0103] Comparative Example 3

[0104] The difference from Example 1 is that the preparation of polyether-modified polyurethane and the preparation of lithium iron phosphate cathode material are carried out simultaneously, as detailed below: Polyether polyol (PEG400) was added to a reactor equipped with a stirrer and heater. A catalyst (dibutyltin dilaurate) was added to the reactor at a rate of 0.05 php, and the mixture was stirred for 30 minutes. Then, 995 parts of ferric phosphate, 226 parts of lithium carbonate, 6.73 parts of an 85 wt% phosphoric acid aqueous solution, 5.97 parts of titanium dioxide, 60 parts of glucose, and 70 parts of polyether-modified polyurethane PU-1 were added. This mixture was then fed into a sand mill (Changzhou Longxin Intelligent Equipment Co., Ltd.'s WSP-0.5) along with the corresponding amount of water. During the sand milling process, isocyanate was added dropwise. The molar ratio of cyanate (toluene diisocyanate), PEG400, and toluene diisocyanate was 3:1. The toluene diisocyanate was added dropwise over 60 minutes, and the temperature was controlled between 25-75℃ throughout the dropwise addition process. After the dropwise addition was completed, the sample was milled for 120 minutes to obtain a precursor slurry with a solid content of 40% and a particle size D50 of 370-380 nm. The carbon source accounted for 9.5% of the total mass, which represents the percentage of the carbon source in the precursor slurry excluding the solvent. The polyether-modified polyurethane accounted for 53.8% of the carbon source. The precursor slurry was spray-granulated in a spray granulation equipment (SP1500 from Shanghai Shunyi Experimental Equipment Co., Ltd.), with an inlet temperature of 220℃ and a material flow rate of 800ml / h. The spray-granulated powder was sintered (using a QLYF-4-1200 sintering equipment from Shanghai Jingzhao Machinery Equipment Co., Ltd.), with a heating rate of 3℃ / min to 720℃ and a holding time of 7h to obtain lithium iron phosphate material.

[0105] The obtained lithium iron phosphate material was crushed to powder with a particle size D50 of 1.2-1.3 μm using a traditional Chinese medicine crusher. The traditional Chinese medicine crusher was a Teruis traditional Chinese medicine pulverizer, and the particle size was tested using a Malvern Panaco Mastersizer-3000 laser particle size analyzer.

[0106] Polyurethane could not be obtained as expected in this comparative example because isocyanate preferentially reacts with water to form polyurea, but cannot react with polyether polyol.

[0107] II. Preparation of Lithium Manganese Iron Phosphate Materials

[0108] Example 6

[0109] 1. Preparation of polyether-modified polyurethane: Same as Example 1.

[0110] 2. Preparation of lithium manganese iron phosphate cathode material: 350 parts lithium carbonate, 1250 parts manganese acetate, 9 parts ferrous oxalate, 40 parts glucose, 60 parts polyether-modified polyurethane PU-1, 12 parts phosphoric acid, and 1000 parts anhydrous ethanol were added to an agate ball mill jar and ball-milled for 4 hours at a ball-to-material ratio of 8:1 to obtain a precursor slurry. The carbon source had a mass percentage of 6.1%, which represents the mass percentage of the carbon source in the precursor slurry excluding the solvent. The polyether-modified polyurethane accounted for 57.1% of the carbon source. The obtained precursor slurry was transferred to an evaporating dish and vacuum dried at 55°C for 8 hours. After grinding through a 100-mesh sieve, it was placed in a tube furnace and argon gas was introduced at a flow rate of 50 mL / min for 30 minutes. The temperature was first increased to 480°C at a rate of 5°C / min and held for 2 hours. Then, the temperature was increased to 700°C at a rate of 3°C / min and held for 8 hours. After sintering, the argon atmosphere was maintained and the mixture was allowed to cool naturally to room temperature. The mixture was then ground in an agate mortar and passed through a 200-mesh sieve to obtain lithium manganese iron phosphate material.

[0111] Example 7

[0112] 1. Preparation of polyether-modified polyurethane: Same as Example 2.

[0113] 2. Preparation of lithium manganese iron phosphate cathode material: 350 parts lithium carbonate, 1250 parts manganese acetate, 9 parts ferrous oxalate, 40 parts glucose, 50 parts polyether-modified polyurethane PU-2, 12 parts phosphoric acid, and 1000 parts anhydrous ethanol were added to an agate ball mill jar and ball-milled for 4 hours at a ball-to-material ratio of 8:1 to 280 r / min to obtain a precursor slurry. The carbon source mass percentage was 5.5%, which represents the mass percentage of the carbon source in the precursor slurry excluding the solvent. The polyether-modified polyurethane accounted for 52.6% of the carbon source mass. The obtained precursor slurry was transferred to an evaporating dish and vacuum dried at 55°C for 8 hours. After grinding through a 100-mesh sieve, it was placed in a tube furnace and argon gas was introduced at a flow rate of 50 mL / min for 30 minutes. The temperature was first increased to 480°C at a rate of 5°C / min and held for 2 hours. Then, the temperature was increased to 700°C at a rate of 3°C / min and held for 8 hours. After sintering, the argon atmosphere was maintained and the mixture was allowed to cool naturally to room temperature. The mixture was then ground in an agate mortar and passed through a 200-mesh sieve to obtain lithium manganese iron phosphate material.

[0114] Example 8

[0115] 1. Preparation of polyether-modified polyurethane: Same as Example 3.

[0116] 2. Preparation of lithium manganese iron phosphate cathode material: 350 parts lithium carbonate, 1250 parts manganese acetate, 9 parts ferrous oxalate, 40 parts glucose, 50 parts polyether-modified polyurethane PU-3, 12 parts phosphoric acid, and 1000 parts anhydrous ethanol were added to an agate ball mill jar and ball-milled for 4 hours at a ball-to-material ratio of 8:1 to obtain a precursor slurry. The carbon source had a mass percentage of 5.5%, which represents the mass percentage of the carbon source in the precursor slurry excluding the solvent. The polyether-modified polyurethane accounted for 52.6% of the carbon source mass. The obtained precursor slurry was transferred to an evaporating dish and vacuum dried at 55°C for 8 hours. After grinding through a 100-mesh sieve, it was placed in a tube furnace and argon gas was introduced at a flow rate of 50 mL / min for 30 minutes. The temperature was first increased to 480°C at a rate of 5°C / min and held for 2 hours. Then, the temperature was increased to 700°C at a rate of 3°C / min and held for 8 hours. After sintering, the argon atmosphere was maintained and the mixture was allowed to cool naturally to room temperature. The mixture was then ground in an agate mortar and passed through a 200-mesh sieve to obtain lithium manganese iron phosphate material.

[0117] Example 9

[0118] 1. Preparation of polyether-modified polyurethane: Same as Example 4.

[0119] 2. Preparation of lithium manganese iron phosphate cathode material: 350 parts lithium carbonate, 1250 parts manganese acetate, 9 parts ferrous oxalate, 40 parts glucose, 45 parts polyether-modified polyurethane PU-4, 12 parts phosphoric acid, and 1000 parts anhydrous ethanol were added to an agate ball mill jar and ball-milled for 4 hours at a ball-to-material ratio of 8:1 to obtain a precursor slurry. The carbon source had a mass percentage of 5.3%, which represents the mass percentage of the carbon source in the precursor slurry excluding the solvent. The polyether-modified polyurethane accounted for 50% of the carbon source. The obtained precursor slurry was transferred to an evaporating dish and vacuum dried at 55°C for 8 hours. After grinding through a 100-mesh sieve, it was placed in a tube furnace and argon gas was introduced at a flow rate of 50 mL / min for 30 minutes. The temperature was first increased to 480°C at a rate of 5°C / min and held for 2 hours. Then, the temperature was increased to 700°C at a rate of 3°C / min and held for 8 hours. After sintering, the argon atmosphere was maintained and the mixture was allowed to cool naturally to room temperature. The mixture was then ground in an agate mortar and passed through a 200-mesh sieve to obtain lithium manganese iron phosphate material.

[0120] Example 10

[0121] 1. Preparation of polyether-modified polyurethane: Same as Example 5.

[0122] 2. Preparation of lithium manganese iron phosphate cathode material: 350 parts lithium carbonate, 1250 parts manganese acetate, 9 parts ferrous oxalate, 40 parts glucose, 60 parts polyether-modified polyurethane PU-5, 12 parts phosphoric acid, and 1000 parts anhydrous ethanol were added to an agate ball mill jar and ball-milled for 4 hours at a ball-to-material ratio of 8:1 to obtain a precursor slurry. The carbon source had a mass percentage of 6.1%, which represents the mass percentage of the carbon source in the precursor slurry excluding the solvent. The polyether-modified polyurethane accounted for 57.1% of the carbon source. The obtained precursor slurry was transferred to an evaporating dish and vacuum dried at 55°C for 8 hours. After grinding through a 100-mesh sieve, it was placed in a tube furnace and argon gas was introduced at a flow rate of 50 mL / min for 30 minutes. The temperature was first increased to 480°C at a rate of 5°C / min and held for 2 hours. Then, the temperature was increased to 700°C at a rate of 3°C / min and held for 8 hours. After sintering, the argon atmosphere was maintained and the mixture was allowed to cool naturally to room temperature. The mixture was then ground in an agate mortar and passed through a 200-mesh sieve to obtain lithium manganese iron phosphate material.

[0123] Comparative Example 4

[0124] Preparation of lithium manganese iron phosphate cathode material: 350 parts lithium carbonate, 1250 parts manganese acetate, 9 parts ferrous oxalate, 40 parts glucose, 50 parts Covestro Impranil DLN SD polyurethane dispersion (solid content 40%), 12 parts phosphoric acid, and 1000 parts anhydrous ethanol were added to an agate ball mill jar and ball-milled for 4 hours at a ball-to-material ratio of 8:1 at a speed of 280 r / min to obtain the precursor slurry. The obtained precursor slurry was transferred to an evaporating dish and vacuum dried at 55°C for 8 hours. After grinding through a 100-mesh sieve, it was placed in a tube furnace and argon gas was introduced at a flow rate of 50 mL / min for 30 minutes. The temperature was first increased to 480°C at a rate of 5°C / min and held for 2 hours. Then, the temperature was increased to 700°C at a rate of 3°C / min and held for 8 hours. After sintering, the argon atmosphere was maintained and the mixture was allowed to cool naturally to room temperature. The mixture was then ground in an agate mortar and passed through a 200-mesh sieve to obtain lithium manganese iron phosphate material.

[0125] Comparative Example 5

[0126] Preparation of lithium manganese iron phosphate cathode material: 350 parts lithium carbonate, 1250 parts manganese acetate, 9 parts ferrous oxalate, 40 parts glucose, 50 parts Lubrizol Sancure 777 waterborne polyurethane (solid content 35%), 12 parts phosphoric acid, and 1000 parts anhydrous ethanol were added to an agate ball mill jar and ball-milled for 4 hours at a ball-to-material ratio of 8:1 at a speed of 280 r / min to obtain the precursor slurry. The obtained precursor slurry was transferred to an evaporating dish and vacuum dried at 55°C for 8 hours. After grinding through a 100-mesh sieve, it was placed in a tube furnace and argon gas was introduced at a flow rate of 50 mL / min for 30 minutes. The temperature was first increased to 480°C at a rate of 5°C / min and held for 2 hours. Then, the temperature was increased to 700°C at a rate of 3°C / min and held for 8 hours. After sintering, the argon atmosphere was maintained and the mixture was allowed to cool naturally to room temperature. The mixture was then ground in an agate mortar and passed through a 200-mesh sieve to obtain lithium manganese iron phosphate material.

[0127] III. Preparation of Sodium Iron Manganese Phosphate Cathode Material for Sodium-Ion Batteries

[0128] Example 11

[0129] 1. Preparation of polyether-modified polyurethane: Same as Example 1.

[0130] 2. Preparation of sodium iron manganese phosphate cathode material: Sodium carbonate, ammonium dihydrogen phosphate, ferric oxide, and manganese dioxide were used as sodium, phosphorus, iron, and manganese sources, respectively. Glucose and polyether-modified polyurethane were mixed in a 1:1 ratio as the carbon source. The molar ratio of sodium, iron, manganese, and phosphorus in the raw materials was controlled at 4:2.98:0.01:4, and the ratio of the molar amount of carbon source (calculated as carbon) to the sum of the molar amounts of iron and manganese was 0.5:1. The raw materials were put into a sand mill and ground at 2000 r / min for 6 h, with a solid content of 50 wt%. The mixture was spray-dried at 250 °C to prepare a dry precursor powder. The precursor powder was placed in a box furnace and calcined at 550 °C for 12 h under N2 atmosphere, followed by natural cooling to obtain the cathode material. The mass percentage of carbon source was 12%, which represents the mass percentage of carbon source in the precursor slurry excluding solvent. The mass percentage of polyether-modified polyurethane in the carbon source was 50%.

[0131] Example 12

[0132] The only difference from Example 11 is that the preparation of polyether-modified polyurethane is the same as in Example 2.

[0133] Example 13

[0134] The only difference from Example 11 is that the preparation of polyether-modified polyurethane is the same as in Example 3.

[0135] Example 14

[0136] The only difference from Example 11 is that the preparation of polyether-modified polyurethane is the same as in Example 4.

[0137] Example 15

[0138] The only difference from Example 11 is that the preparation of polyether-modified polyurethane is the same as in Example 5.

[0139] Comparative Example 6

[0140] Sodium carbonate, ammonium dihydrogen phosphate, ferric oxide, and manganese dioxide were used as sodium, phosphorus, iron, and manganese sources, respectively. Glucose and Covestro Impranil DLN SD polyurethane dispersion (40% solid content) were mixed in a 1:1 mass ratio as a carbon source. The molar ratio of sodium, iron, manganese, and phosphorus in the raw materials was controlled at 4:2.98:0.01:4, and the ratio of the molar amount of carbon source (calculated as carbon) to the sum of the molar amounts of iron and manganese was 0.5:1. The raw materials were put into a sand mill and ground at 2000 r / min for 6 h, with a solid content of 50 wt% during grinding. The mixture was spray-dried at 250 °C to prepare a dry precursor powder. The precursor powder was placed in a box furnace and calcined at 550 °C for 12 h under N2 atmosphere, followed by natural cooling to obtain the cathode material.

[0141] Comparative Example 7

[0142] Sodium carbonate, ammonium dihydrogen phosphate, ferric oxide, and manganese dioxide were used as sodium, phosphorus, iron, and manganese sources, respectively. Glucose and Lubrizol Sancure 777 waterborne polyurethane (35% solid content) were mixed in a 1:1 mass ratio as a carbon source. The molar ratio of sodium, iron, manganese, and phosphorus in the raw materials was controlled at 4:2.98:0.01:4, and the ratio of the molar amount of carbon source (calculated as carbon) to the sum of the molar amounts of iron and manganese was 0.5:1. The raw materials were put into a sand mill and ground at 2000 r / min for 6 h, with a solid content of 50 wt% during grinding. The mixture was prepared into a dry precursor powder at 250 °C using a spray drying method. The precursor powder was placed in a box furnace and calcined at 550 °C for 12 h under a N2 atmosphere, followed by natural cooling to obtain the cathode material.

[0143] Example 1

[0144] 1. Structural characterization

[0145] Infrared spectroscopy was performed on the polyether-modified polyurethanes prepared in Examples 1-5. A Nicolet iG50 FTIR spectrometer was used. ATR mode was activated, and the air background was tested. The polyether-modified polyurethane was dropped onto a diamond crystal on the ATR module, and the crystal was analyzed at 400 cm⁻¹. -1 -4000cm -1 The area was scanned 32 times, with a resolution of 4cm. -1 The result is as follows Figure 1-5 As shown. Figure 1 The infrared spectrum of the polyether-modified polyurethane prepared in Example 1 is shown below. Figure 2 The infrared spectrum of the polyether-modified polyurethane prepared in Example 2 is shown below. Figure 3 The infrared spectrum of the polyether-modified polyurethane prepared in Example 3 is shown below. Figure 4 The infrared spectrum of the polyether-modified polyurethane prepared in Example 4 is shown below. Figure 5 The image shows the infrared spectrum of the polyether-modified polyurethane prepared in Example 5.

[0146] Depend on Figure 1-5 As shown, the polyether-modified polyurethanes prepared in Examples 1-5 all have a diameter of 3325 cm⁻¹. -1 There is an NH stretching vibration peak nearby, at 1690 cm⁻¹. -1 There is a C=O stretching vibration peak of carbamate nearby, at 1532 cm⁻¹. -1 The presence of characteristic peaks for amides nearby indicates successful polyurethane bond formation. Simultaneously, at 1100 cm⁻¹... -1 The presence of a strong absorption peak for the COC stretching vibration of the polyether chain nearby indicates that the polyether reaction is complete.

[0147] 2. Molecular weight and PDI testing

[0148] The molecular weight and PDI of the polyether-modified polyurethanes prepared in Examples 1-5 were determined using Waters 1515 gel permeation chromatography (GPC) and a Waters 2414 refractive index detector.

[0149] The testing method was as follows: First, a polyether-modified polyurethane solution with a concentration of 1.5 mg / mL was prepared. Tetrahydrofuran (THF) was used as the mobile phase, and polyethylene glycol (PEG) of different molecular weights was used as standard samples to generate a standard curve. The spectral results were then processed. The results are as follows: Figure 6-10 As shown. Figure 6 The graph shows the molecular weight and PDI test results of the polyether-modified polyurethane PU-1 prepared in Example 1. Figure 7 The graph shows the molecular weight and PDI test results of the polyether-modified polyurethane PU-2 prepared in Example 2. Figure 8 The graph shows the molecular weight and PDI test results of the polyether-modified polyurethane PU-3 prepared in Example 3. Figure 9 The graph shows the molecular weight and PDI test results of the polyether-modified polyurethane PU-4 prepared in Example 4. Figure 10 The graph shows the test results of molecular weight and PDI of the polyether-modified polyurethane PU-5 prepared in Example 5. According to the test results, the weight-average molecular weights of PU-1, PU-2, PU-3, PU-4, and PU-5 are 2015, 3597, 2833, 2367, and 2519, respectively; the PDIs of PU-1, PU-2, PU-3, PU-4, and PU-5 are 1.038560, 1.102502, 1.102931, 1.046140, and 1.031904, respectively.

[0150] Example 2

[0151] 1. The residual carbon content of the lithium iron phosphate materials prepared in the examples and comparative examples was tested using a Shanghai Dekai HCS-140 high-frequency infrared carbon-sulfur analyzer.

[0152] 2. The powder resistivity and compaction density of lithium iron phosphate materials prepared in the examples and comparative examples were tested using Xiamen Yuaneng four-probe powder resistivity PRCD2110.

[0153] The test results are shown in Table 1.

[0154] 3. Microscopic morphological observation

[0155] The surface morphology of lithium iron phosphate materials prepared in the examples and comparative examples was characterized using a Tesken MIRA3 field emission scanning electron microscope. Before testing, the lithium iron phosphate materials were dried and directly dispersed on conductive adhesive without additional coating treatment, then fixed on the sample stage for observation. Surface morphology images were acquired using a secondary electron detector, with an accelerating voltage set to a low voltage of 3-5 kV and a working distance set to 8-10 mm. The results are as follows: Figure 11 and Figure 12 As shown.

[0156] Figure 11 This is a SEM image of the lithium iron phosphate material prepared in Example 1. Figure 12 This is a SEM image of the lithium iron phosphate material prepared in Comparative Example 1. Figure 11 and Figure 12 The comparison shows that the lithium iron phosphate material prepared in the comparative example has more uncoated carbon sources, which are distributed in a mesh-like pattern on the surface of the lithium iron phosphate material, indicating poor coating ability; conversely, the lithium iron phosphate material prepared in the example has fewer uncoated carbon sources in a mesh-like pattern on the surface, indicating more uniform coating.

[0157] 4. The powder conductivity of lithium manganese iron phosphate materials prepared in the examples and comparative examples was tested using Xiamen Yuaneng four-probe powder resistivity PRCD2110.

[0158] The test results are shown in Table 2.

[0159] Example 3

[0160] 1. Batteries prepared using lithium iron phosphate as the positive electrode active material

[0161] The crushed lithium iron phosphate material (LiFePO4) obtained in the above examples and comparative examples was mixed with the above raw materials in a mass ratio of LiFePO4:conductive carbon black:polyvinylidene fluoride (PVDF) = 8:1:1. N-methylpyrrolidone was added to prepare a positive electrode slurry with a solid content of 55%. This slurry was uniformly coated onto carbon-coated aluminum foil, vacuum dried, rolled, and punched into a 2.01 cm² area. 2 Electrode assembly. The negative electrode uses a lithium metal sheet, the separator uses Celgard 2400PE film, and the electrolyte uses a commercially available product (SS-SHRG004, Dongguan Shanshan Battery Materials Co., Ltd.). The positive electrode, separator, and negative electrode are assembled in one go in a glove box (high-purity Ar atmosphere), and then the electrolyte (1 mol / L NaClO4 + EC:DMC:EMC(1:1:1) + 5% FEC) is injected to obtain a coin cell.

[0162] The coin cell was subjected to constant current charge-discharge cycle test at 25℃ and 0.1C, with a charge-discharge voltage of 2.0-3.7V. The initial coulombic efficiency was calculated. There was no special test method. The initial coulombic efficiency = initial discharge specific capacity / initial charge specific capacity. The coin cell battery was tested for rate capability at 25℃ and 2C. The test results are shown in Table 1.

[0163] Table 1

[0164] As can be seen from the test results in Table 1, compared with the cathode material prepared using commercially available waterborne polyurethane as a carbon source, the cathode material prepared using polyether-modified polyurethane in Examples 1-5 has a significantly lower powder resistivity and a higher compaction density under the same residual carbon content. The first discharge capacity, first coulombic efficiency, and 2C rate performance of the resulting coin cells are significantly improved, indicating that the cathode material prepared using polyether-modified polyurethane in Examples 1-5 as one of the carbon sources has excellent coin cell performance.

[0165] 2. Batteries prepared using lithium manganese iron phosphate as the positive electrode active material

[0166] 85g of lithium manganese iron phosphate material, 5g of polyvinylidene fluoride, 10g of conductive carbon black, and 150mL of N-methylpyrrolidone prepared in the above examples and comparative examples were placed in a beaker and mechanically stirred at 500r / min for 4h to form a slurry. The slurry was coated onto aluminum foil with a single-sided thickness of 80μm using a doctor blade coater. The foil was first pre-dried in a 60℃ forced-air drying oven for 30min, and then transferred to a 120℃ vacuum drying oven for 12h. The dried electrode was compacted using a roller press with a pressure controlled at 110MPa and cut into electrode sheets with a diameter of 14mm to obtain the positive electrode. Using lithium foil as the negative electrode and a Celgard 2400 polypropylene microporous membrane as the separator, and 1 mol / L LiPF6 (EC:DEC = 1:1, v / v) as the electrolyte, the positive electrode, negative electrode, separator, and electrolyte were assembled in an argon glove box with water and oxygen content all below 1 ppm. After assembly, the cells were allowed to stand for 24 hours to obtain coin cells. The discharge specific capacity at 0.1C and 5C rates was tested under charge / discharge cutoff voltages of 3.0-4.3V; the capacity retention rate after 100 cycles at 5C charge / discharge rate was also tested. The results are shown in Table 2.

[0167] Table 2

[0168] As can be seen from the test results in Table 2, compared with the cathode material prepared using commercially available waterborne polyurethane as a carbon source, the cathode material prepared using the polyether-modified polyurethane of Examples 6-10 has a significantly improved powder conductivity, and the discharge specific capacity and capacity retention of the coin cells prepared are significantly improved. This indicates that the cathode material prepared using the polyether-modified polyurethane of Examples 6-10 as one of the carbon sources has excellent coin cell performance.

[0169] 3. Batteries prepared using sodium iron manganese phosphate (sodium iron manganese phosphate) as the positive electrode active material for sodium-ion batteries.

[0170] The sodium-ion batteries prepared in the above examples and comparative examples were uniformly mixed with sodium iron manganese phosphate positive electrode material, acetylene black, and PVDF binder, and then coated onto aluminum foil. After vacuum baking at 100°C for 4 hours, electrode sheets were obtained. Based on the total weight of the positive electrode material, acetylene black, and PVDF binder, the amount of positive electrode material was 80 wt%, the amount of acetylene black was 10 wt%, and the amount of PVDF binder was 10 wt%. Using the sodium sheet as the negative electrode, a glass fiber optic GF / A Whatman potassium sodium lithium battery filter membrane was used as the separator, and a 0.8 M NaPF6 / EC-DMC electrolyte was used. Button batteries were assembled and their charge-discharge characteristics were tested. The charge-discharge current was 0.1C, where 1C = 129 mA / g. The discharge specific capacity and average discharge voltage of the comparative and examples are shown in Table 3.

[0171] Table 3

[0172] As can be seen from the test results in Table 3, compared with the cathode material prepared using commercially available waterborne polyurethane as a carbon source, the coin cell prepared using the cathode material prepared by the polyether-modified polyurethane in Examples 11-15 has significantly improved specific capacity and capacity retention, indicating that the cathode material prepared by using the polyether-modified polyurethane in Examples 11-15 as one of the carbon sources has excellent coin cell performance.

[0173] While specific embodiments of the present invention have been described above, those skilled in the art should understand that these are merely illustrative examples, and the scope of protection of the present invention is defined by the appended claims. Those skilled in the art can make various changes or modifications to these embodiments without departing from the principles and essence of the present invention, but all such changes and modifications fall within the scope of protection of the present invention.

Claims

1. A method for preparing a positive electrode material, characterized in that, It includes the following steps: The precursor slurry is sintered to obtain the cathode material; the precursor slurry includes a carbon source; the carbon source includes polyether-modified polyurethane. The polyether-modified polyurethane is prepared using polyether polyol and isocyanate as raw materials.

2. The method for preparing the cathode material as described in claim 1, characterized in that, The method for preparing the cathode material satisfies one or more of the following conditions: (1) The weight-average molecular weight of the polyether-modified polyurethane is 2000-5000, preferably 2010-4000, for example 2015, 3597, 2833, 2367 or 2519; (2) The PDI of the polyether-modified polyurethane is 1.00-2.00, preferably 1.03-1.20, for example 1.038560, 1.102502, 1.102931, 1.046140 or 1.031904; (3) The polyether polyol is a polyether diol and / or a polyether triol; (4) The hydroxyl value of the polyether polyol is 20-500 mgKOH / g, preferably 30-300 mgKOH / g, for example 280.5, 38.9, 42.3 or 190.4 mgKOH / g; (5) The isocyanate is toluene isocyanate and / or toluene diisocyanate; The toluene isocyanate is preferably one or more of o-toluene isocyanate, m-toluene isocyanate and p-toluene isocyanate, such as m-toluene isocyanate; Wherein, the toluene diisocyanate is a mixture of toluene-2,4-diisocyanate and toluene-2,6-diisocyanate; the mass ratio of toluene-2,4-diisocyanate and toluene-2,6-diisocyanate is preferably (1-6):1, for example 1:1; (6) The molar ratio of the polyether polyol to the isocyanate is (1-15):1, preferably (1-10):1, for example 1:1, 2:1, 3:1 or 4:1; (7) The raw materials for the polyether-modified polyurethane also include a catalyst; The catalyst is preferably a tin-based catalyst and / or an amine-based catalyst; the tin-based catalyst is preferably dibutyltin dilaurate and / or stannous octoate; the amine-based catalyst is preferably triethylenediamine. The catalyst is preferably used in an amount of 0.01-5.0 php, more preferably in an amount of 0.03-0.3 php, such as 0.05, 0.07, 0.13, 0.25 or 0.19 php; where php refers to the mass percentage of the catalyst in the polyether polyol and isocyanate.

3. The method for preparing the cathode material as described in claim 2, characterized in that, The method for preparing the cathode material satisfies one or more of the following conditions: (1) The polyether diol has the structure described in Formula I: Equation I; In Formula I, the values ​​of a, b, and c are each independently between 0 and 500, and a, b, and c cannot be 0 simultaneously; preferably, a = c; a is preferably between 10 and 50, for example, 13; b is preferably between 10 and 50, for example, 30; c is preferably between 10 and 50, for example, 13; (2) The polyether diol has the structure described in Formula II: Formula II; In Formula II, the values ​​of d, e, and f are each independently 0-500, and a, b, and c cannot be 0 simultaneously; preferably, d=f; the value of d is preferably 10-50, for example 14; the value of e is preferably 10-50, for example 24; the value of f is preferably 10-50, for example 14. (3) The polyether triol has the structure described in Formula III: Formula III; In Formula III, R1, R2 and R3 are each independently selected from -H, -CH3 or -CH2CH3; the values ​​of g, h and i are each independently 0-500 and g, h and i cannot be 0 at the same time; g is preferably 1-20, for example 6; h is preferably 1-20, for example 6; i is preferably 1-20, for example 6.

4. The method for preparing the cathode material as described in claim 1, characterized in that, The method for preparing the cathode material satisfies any one of the following conditions: (1) The polyether-modified polyurethane is prepared using polyethylene glycol 400, toluene diisocyanate and dibutyltin dilaurate as raw materials; (2) The polyether-modified polyurethane is prepared using propylene glycol block polyether Pluronic L64, toluene diisocyanate and stannous octoate as raw materials. (3) The polyether-modified polyurethane is prepared using trans polyether Pluronic 17R4, toluene diisocyanate and stannous octoate as raw materials. (4) The polyether-modified polyurethane is prepared using glycerol polyoxyethylene ether G18, toluene diisocyanate and triethylenediamine as raw materials; (5) The polyether-modified polyurethane is prepared using glycerol polyoxyethylene ether G18, m-toluene isocyanate and dibutyltin dilaurate as raw materials.

5. The method for preparing the cathode material as described in claim 1, characterized in that, The preparation method of the polyether-modified polyurethane includes the following steps: adding the isocyanate dropwise to a mixture of the polyether polyol and the catalyst, and reacting; The mixture of polyether polyol and catalyst is preferably obtained by mixing and stirring the polyether polyol and catalyst; the stirring time is preferably 30-120 min, for example 30, 40 or 50 min. The preferred dripping time for the isocyanate is 30-100 min, for example, 40, 50, 60, 70 or 90 min; The temperature of the system during the dropwise addition of the isocyanate is preferably 25-75°C. The reaction temperature is preferably 25-75°C, for example 50, 55, 65, 70 or 75°C; The reaction time is preferably 60-120 min, for example 60, 80, 90, 100 or 120 min.

6. The method for preparing the cathode material as described in claim 1, characterized in that, The method for preparing the cathode material satisfies any one of the following conditions: (1) The mass percentage of the carbon source is 3-15%, preferably 5-12%, for example 9.5%, 8.9%, 8.2%, 6.1%, 5.5%, 5.3% or 12%; the mass percentage represents the mass percentage of the carbon source in the precursor slurry excluding the solvent. (2) The polyether-modified polyurethane accounts for 30-70% of the mass percentage of the carbon source, preferably 45-60%, for example 53.8%, 50%, 45.5%, 57.1% or 52.6%; (3) The carbon source also includes other carbon sources, preferably one or more of sucrose, glucose, polyethylene glycol, starch, citric acid and asphalt, such as polyethylene glycol and / or glucose; the polyethylene glycol is preferably PEG1500, PEG6000 or PEG-200; The carbon source preferably includes glucose and the polyether-modified polyurethane; the mass ratio of glucose to the polyether-modified polyurethane is preferably (0.3-2):1, more preferably (0.5-1.5):1, for example 6:7, 0.75:1, 0.9:1, 1:1 or 1.2:

1.

7. The method for preparing the cathode material as described in claim 1, characterized in that, The method for preparing the cathode material satisfies any one of the following conditions: (1) The positive electrode material is lithium iron phosphate, lithium manganese iron phosphate or sodium iron manganese phosphate; (2) The sintering temperature is 300-850℃, preferably 400-750℃, for example 480, 550, 700 or 720℃; (3) The sintering time is 1-20h, preferably 2-13h, for example 2, 7, 8 or 12h; (4) The heating rate from room temperature to the sintering temperature is 1-10℃ / min, preferably 2-6℃ / min, for example 3 or 5℃ / min.

8. A positive electrode material, characterized in that, It is prepared using the method for preparing the cathode material as described in any one of claims 1-7.

9. An electrode sheet, characterized in that, It includes the cathode material as described in claim 8.

10. A battery, characterized in that, It includes the electrode as described in claim 9.